Thermally Drawn Highly Conductive Fibers with Controlled Elasticity. Issue 19 (5th April 2022) - Marion, Juliette S.; Gupta, Nikhil; Cheung, Henry; Monir, Kirmina; Anikeeva, Polina; Fink, Yoel
Abstract: Electronic fabrics necessitate both electrical conductivity and, like any textile, elastic recovery. Achieving both requirements on the scale of a single fiber remains an unmet need. Here, two approaches for achieving conductive fibers (10 7 S m −1 ) reaching 50% elongation while maintaining minimal change in resistance (<0.5%) in embedded metallic electrodes are introduced. The first approach involves inducing a buckling instability in a metal microwire within a cavity of a thermally drawn elastomer fiber. The second approach relies on twisting an elastomer fiber to yield helical metal electrodes embedded in a stretchable yarn. The scalability of both approaches is illustrated in apparatuses for continuous buckling and twisting that yield tens of meters of elastic conducting fibers. Through experimental and analytical methods, it is elucidated how geometric parameters, such as buckling pre‐strain and helical angle, as well as materials choice, control not only the fiber's elasticity but also its Young's modulus. Links between mechanical and electrical properties are exposed. The resulting fibers are used to construct elastic fabrics that contain diodes, by weaving and knitting, thus demonstrating the scalable fabrication of conformable and stretchable antennas that support optical data transmission. Abstract : Elasticity is introduced in thermally drawn fibers by modifying the pathway of metallic electrodes to either a buckled or helical configuration. The electrodes maintain minimal change in resistance within the elastic strain regime defined by geometric and material properties. Integration of light‐emitting diodes connected by stretchable electrodes within fibers yields stretchable and conformable fabric optical antennas for high‐bandwidth data transmission.